Pengaruh motivasi, kepuasan, dan disiplin kerja terhadap kinerja karyawan pada PT. Indonesia Comnets Plus Medan - Faisal Mirza, Deni; Swarni Lumbantobing, Titi Swarni Lumbantobing; Perary Menzez Simanjuntak, Heny; Giawa, Yosafati (Jurnal Paradigma Ekonomika, 2021)
The purpose of the implementation of the research is to understand the magnitude of the influence of free or independent variables of job satisfaction, work discipline and also motivation on performance generated by employees working in PT. Indonesia Comnets Plus. In the implementation of this study, the population used was 60 officers and while the sample was as many as 60 survey respondents. In the implementation of this research, the method used is a quantitative approach, and while for this research technique uses multiple linear analysis. The results of this research conducted show that simultaneously or together that variables are free or independent of job satisfaction, work discipline and also motivation contributes a significant influence on the performance produced by employees working in PT. Indonesia Comnets Plus, meanwhile, partially tested results showed that variables free or independent of job satisfaction, work discipline and motivation contributed significantly to the performance generated by employees working at PT. Indonesia Comnets Plus. The ongoing relationship between free or independent variables of job satisfaction, work discipline and also motivation on variables is bound or dependent from performance generated by employees working at PT. Indonesia Comnets Plus is very large. Â